Viṣṇu Khare - Caudharī, Aṃśu Kumāra,Śarmā, Śubhrā (Prabhākara Prakāśana, 2021)
Contributed articles on the life and poetic works of Vishṇu Khare, 1940-2018, Hindi author.
Includes bibliographical references
Keywords: Khare; Vishṇu; 1940-2018; Poetic works.